2020
DOI: 10.5664/jcsm.8476
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in positive airway pressure therapy adherence among veterans with obstructive sleep apnea

Abstract: Study Objectives: Black individuals are disproportionately affected by diabetes, cardiovascular disease, obesity, and OSA. Adherence to PAP therapy has been reported to be lower among black individuals. This study seeks to examine associations between black race and PAP adherence among veterans with OSA. Methods: This was a retrospective study. Veterans newly diagnosed with OSA at a single Department of Veterans Affairs sleep center who were prescribed a modem-enabled PAP device between January 2015 and Novemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
7
1
Order By: Relevance
“…44 A more recent study of veterans who received treatment in a VA sleep disorders center found that Black race was associated with less PAP use (compared to White race) over the first 30 days of treatment, but again, the study sample was 95% male veterans. 45 We did not find differences in PAP use among women veterans based on racial/ ethnic identity. Another study found worse PAP adherence in younger women (ages 18-30) compared to women in other age ranges and compared to men in a national sample, 46 but age was not different in users and nonusers of PAP in our study.…”
Section: Discussioncontrasting
confidence: 58%
“…44 A more recent study of veterans who received treatment in a VA sleep disorders center found that Black race was associated with less PAP use (compared to White race) over the first 30 days of treatment, but again, the study sample was 95% male veterans. 45 We did not find differences in PAP use among women veterans based on racial/ ethnic identity. Another study found worse PAP adherence in younger women (ages 18-30) compared to women in other age ranges and compared to men in a national sample, 46 but age was not different in users and nonusers of PAP in our study.…”
Section: Discussioncontrasting
confidence: 58%
“…7,8 In older adults with OSA, the proportions of PAP treated and PAP adherent are estimated between 60% and 73%. [9][10][11] Sociodemographic and health factors have been linked to OSA treatment gaps, 10,12,13 but data on regional OSA disparities in the United States are scarce. 14 Geographic differences have been reported in other chronic conditions such as metabolic syndrome and stroke recurrence and mortality, with the highest burden observed in central US states, the Southeast, and the Northeast, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Higher residual apnea-hypopnea index (AHI) (poor efficacy of CPAP delivery) and poor self-efficacy (which involves volition, motivation, and confidence to engage in a healthy behavior) were the significant predictors of “early” nonadherence (during the first two weeks) [ 9 , 10 , 13 ]. On the other hand, long-term nonadherence with CPAP therapy has been associated with the use of CPAP for <4 hours/night during early treatment [ 7 ], moderate to severe OSA [ 11 , 12 , 15 ], lack of a passionate perspective about the benefit of CPAP therapy [ 16 , 17 ], poor self-efficacy [ 7 , 15 - 17 ], and unsupportive bed partner [ 15 ].…”
Section: Reviewmentioning
confidence: 99%